Structure and Properties of Cartilage Proteoglycans. Issue 1 (April 2017) - Horkay, Ferenc; Basser, Peter J.; Hecht, Anne‐Marie; Geissler, Erik
Summary: The most abundant cartilage proteoglycan is aggrecan, a bottlebrush shaped molecule that possesses over 100 glycosaminoglycan (chondroitin sulfate and keratan sulfate) chains. The side‐chains are linear sulfated polysaccharides that are negatively charged under physiological conditions. Aggrecan interacts with hyaluronic acid (HA) to form large aggregates. Osmotic pressure measurements and rheological measurements are used to study the static and dynamic behavior of aggrecan assemblies at the macroscopic length scales. The microscopic properties of aggrecan solutions are determined by small angle neutron scattering, and static and dynamic light scattering (SLS and DLS). In dilute solutions aggrecan forms microgels with a diffuse boundary, composed of loosely connected clusters. The osmotic pressure of the aggrecan‐HA system decreases with increasing HA content. DLS yields a relaxation rate that varies as q 3, arising from internal modes in the microgel. The relaxation rate in the solutions of the aggrecan‐HA complex is slightly greater than in the pure aggrecan solution.